DIFFERENCES IN THE FREQUENCY OF NAUSEA VOMITING IN FIRST-TRIMESTER PREGNANT WOMEN WHO CONSUME WARM GINGER AND HONEY GINGER IN THE WORKING AREA OF THE MANDALAWANGI HEALTH CENTER IN 2023 - Asriyani, Aditia Putri; Galaupa, Resi (HEARTY, 2025)
Until now the high maternal mortality rate in Indonesia is still a priority issue in the health sector. In pregnancy, nausea and vomiting can adversely affect pregnant women because it can lead to dehydration, electrolyte imbalances and can result in death. Alternative treatments to overcome nausea and vomiting can provide therapy from natural ingredients, namely ginger and honey. This study aims to determine the difference in the frequency of nausea and vomiting after administration of ginger and honey in first trimester pregnant women in Mangkualam village in the work area of Cimanggu Health Center in Pandeglang District in 2023. The research design used was quasi experimental with pre and post test group design. The sample in this study amounted to 20 respondents with the sampling technique in the study using total sampling technique that is taking a sample as a whole that meets the inclusion and exclusion criteria. In this study, the instrument in this study used Index Nausea Vomiting and Retching (INVR) to measure the scale of nausea and vomiting and ginger and honey to reduce nausea and vomiting. The results showed that there were significant differences between pregnant women before and after consuming ginger and honey with the results (p value <0.05). Ginger and honey can be used as an alternative medicine for pregnant women who experience nausea and vomiting from natural ingredients.